2023
DOI: 10.1111/dom.15187
|View full text |Cite
|
Sign up to set email alerts
|

Combining polygenic risk scores and human leukocyte antigen variants for personalized risk assessment of type 1 diabetes in the Taiwanese population

Wen‐Ling Liao,
Yu‐Nan Huang,
Ya‐Wen Chang
et al.

Abstract: AimsTo analyse the genome‐wide association study (GWAS) data of patients with type 1 diabetes mellitus (T1D) in order to develop a risk score for the genetic effects on T1D risk and age at diagnosis in the Taiwanese population.Materials and MethodsWe selected 610 patients with T1D and 2511 healthy individuals from an electronic medical record database of more than 300 000 individuals with genetic information, analysed their GWAS data, and developed a polygenic risk score (PRS).ResultsThe PRS, based on 149 sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In Taiwan, few studies have been conducted on the use of PRS for the treatment of psoriasis. Evidence suggests that diabetes mellitus is increasingly prevalent among patients with psoriasis ( 22 , 156 , 157 ). Eiris et al ( 158 ) showed a significant association between three SNPs (rs6887695, rs3212227 and rs2201841) and diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Taiwan, few studies have been conducted on the use of PRS for the treatment of psoriasis. Evidence suggests that diabetes mellitus is increasingly prevalent among patients with psoriasis ( 22 , 156 , 157 ). Eiris et al ( 158 ) showed a significant association between three SNPs (rs6887695, rs3212227 and rs2201841) and diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…The PRS, clinical data, or a combination of both was used to construct logistic regression models. The models were subsequently adjusted for sex, age, HLA-A*02:07 and HLA-C*06:02 ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each clump comprised SNPs located within 250 kb of the index SNP and in linkage disequilibrium with the index SNP, based on pairwise threshold of r 2 = 0.1. A candidate PRS was computed using the resultant index SNPs and the corresponding estimated OR coefficients for its effect allele as weights using the "score" procedure in the GWAS of the base group [ 35 ].…”
Section: Methodsmentioning
confidence: 99%